Organizational Redesign, Information Technologies and Workplace Productivity - Benoit Dostie; Rajshri Jayaraman (European School of Management and Technology (ESMT), 2008)
Using a large longitudinal, nationally representative workplace-level dataset, we explore the productivity gains associated with computer use and organizational redesign. The empirical strategy involves the estimation of a production function, augmented to account for technology use and organizational design, correcting for unobserved heterogeneity. We find large returns associated with computer use. We also find that computer use and organizational redesign may be complements or substitutes in production, and that the productivity gains associated with organizational redesign are industry-specific.
urn:nbn:de:101:1-201106143518
Keywords: D20; L20; M54; O33; 650; organizational capital; IT; computers; workplace productivity; matched employer-employee data